Objective methods in postlingually and prelingually deafened adults for programming cochlear implants: ESR and NRT - Polak, Marek; Hodges, Annelle V.; King, John E.; Payne, Stacy L.; Balkany, Thomas J. (Cochlear implants international, 2006)
This study compared responses of prelingually and postlingually deafened adult Nucleus 24 cochlear implant users on two objective measures employed to predict programming levels: neural response telemetry (NRT) and electrically evoked stapedial reflexes (eSR). Thirty experienced postlingually and prelingually deafened adult implant users underwent standard behavioural judgements of maximum comfortable loudness levels (C levels) and thresholds (Ts) followed by eSR and NRT measurements. Two different programs were created based on both the subjective judgement and the objective estimates of C levels (eSR thresholds) and these were compared. Relationships between the subjective and the objective measures were statistically analysed. Maximum stimulation levels estimated by both eSR and NRT were highly correlated with C levels. Variability of NRT results was higher than for eSR results. Mean NRT thresholds for postlingually deafened patients were higher than for prelingually deafened patients. A number of prelingually deafened users could distinguish no difference between programs; however, the majority of postlingually deafened users were sensitive to the difference and many reported preference for the program with eSR-estimated C levels. Neural response telemetry thresholds and eSRTs obtained in Nucleus 24 patients are highly correlated with C levels and Ts. Results suggest that estimation of C levels and Ts using NRT or eSR requires different correction factors for prelingually versus postlingually deafened adult subjects. Copyright © 2006 John Wiley & Sons, Ltd.